Compliance with the Code of Conduct and Teaching Performance (International Journal of Scientific Research and Management (IJSRM), 2023)
The main purpose of this study was to determine the compliance with the code of conduct and teaching performance of 347 public elementary teachers of 6th Congressional District of Negros Occidental using stratified random sampling. The descriptive research design was used. The modified survey questionnaire adapted from the study of Jongue (2010) and approved Individual Performance Commitment and Review Form (IPCRF) for S.Y. 2015-2016 was utilized to get the needed data. The data collected was analyzed using frequency and percentages, mode and Pearson-r correlation coefficient. Moreover, Focus Group Discussion (FGD) with 10 participants was utilized to enrich and supplement the results of the study. Results revealed that in terms of profile, majority of the participants were female, ages 31-40 and 11-20 years in length of service. For the teaching position, majority of the participants were Teacher 1 and Bachelor degree holders. For school location, majority of the participants were in the municipality. Furthermore, findings showed that the extent of the compliance with the code of conduct of the participants was “Always” and their overall teaching performance was very satisfactory. The study found significant differences in the variables and grouped according to the code of conduct. Finally, there were significant relationships found in various components of code of conduct and teaching performance. Recommendations on the findings for the capacity build-up of the participants in complying the code of conduct and teaching performance were given. Lastly, a Teachers Development Program (TDP) was proposed.